'LDL-C' = LDL-C + Lp(a)-C. Issue 3 (June 2015) - Yeang, Calvin; Witztum, Joseph L.; Tsimikas, Sotirios
<x xml:space="preserve">Abstract</x> Purpose of review The measurement that is termed 'LDL-cholesterol' (LDL-C) includes the cholesterol content of lipoprotein(a) [Lp(a)-C], which can contribute approximately 30–45% to measured LDL-C levels as a percentage of its mass. We review the implications of achieved very low LDL-C levels in patients treated with potent LDL-C-lowering agents in the context of varying Lp(a) levels. Recent findings Combination therapy with statins, ezetimibe, and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors can lower LDL-C to unprecedentedly low levels. Recent PCSK9 trials have shown that routine achievement of mean LDL-C less than 50 mg/dl is feasible, along with the modest reductions in Lp(a). Many patients will achieve LDL-C less than 25 mg/dl with concomitantly elevated Lp(a) levels that contribute substantially to the measured 'LDL-C'. Therefore, it is possible that some of these patients may have little to no circulating LDL-C. Summary As the new era of ultralow LDL-C levels ensues, it is imperative to understand the contribution of Lp(a)-C to measured LDL-C and the consequences of achieving ultralow or potentially absent LDL-C in the setting of elevated Lp(a) levels and possibly free apo(a). We review this concept and suggest avenues of research, including analyses of existing datasets in current clinical trials and new research studies, to understand its pathophysiological and clinical significance.